PENGARUH INVESTASI, TENAGA KERJA, DAN PENDAPATAN ASLI DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO PROVINSI JAWA TENGAH - Sigit Aji Pamungkas; Diah Retnowati; Zumaeroh (Majalah Imiah Manajemen & Bisnis, 2019)
Gross Regional Domestic Product (GRDP), seen as a very important indicator because it has many benefits relating to economic progress and development, excellence, and weakness in various sectors in the economic structure. The level of progress and development can be seen from the results of economic activities by comparing sectors that make the biggest contribution to the formation of Gross Regional Domestic Product (GRDP) in Central Java. From developments in a certain period can also be observed the advantages and disadvantages of the economic structure of an area. The economy in Central Java can be seen from the large number of contributions to GRDP. Sectors that contribute substantial income or added value to the GRDP, include the domestic investment sector, labor and local revenue. Therefore this study aims to determine the magnitude of the influence of domestic investment, labor, and local revenue on the growth of Central Java GRDP in 2011-2015. The type of data used in this study is secondary data that functions panel from 2011-2015 and the data is obtained from the Central Statistics Agency (BPS). This study uses a vector error correction model panel analysis (PVECM) using the Eview9 program tool. Research Results Establish that PMDN and labor have positive short-term and long- term positive relationships with GRDP. While regional original revenues have negative short- term and long-term negatives of GDP, based on the results of the PVECM